Blancanieves [videorecording (DVD)] - Berger, Pablo; Berger, Pablo; Verdú, Maribel, 1970-; Giménez Cacho, Daniel; Oria, Sofía (2013)
"Once upon a time there was a little girl named Carmen, who never knew her mother. She learned the art of her father, a famous bullfighter, but was hated by her evil stepmother. One day she ran away with a troupe of dwarves, and became a legend. A re-telling of the classic 'Snow White'"--Container.